Pengembangan Bahan Ajar Berorientasi Asesmen Kompetensi Minimum (AKM) dan Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Hasil Belajar Kognitif pada Pembelajaran IPA di Sekolah Dasar - Andrian Pratipto; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
The purpose of this study was to develop, describe the level of feasibility, find out user responses and find out the effectiveness of AKM learning materials to improve students' cognitive learning outcomes. The type of research used is research and development (Research and development). The research model in the development of teaching materials is the ADDIE model. The types of data used are quantitative and qualitative data with instruments: interviews, needs analysis, questions, expert validation sheets and user response questionnaires. Based on the results of the study it was concluded that the AKM-oriented teaching materials and the CTL approach developed were suitable for use as teaching materials in Class V Natural Sciences (IPA) content on water cycle materials. Expert validation was carried out for aspects of material feasibility, language, and design. Percentage of validation results of material aspects (67%), language (78%) and design 78%. Based on the results of the student response questionnaire to the subject matter from the presentation aspect, the proportion was 87% in the high category, the material aspect was 87% in the high category and the language aspect was 88% in the high category. AKM-oriented teaching materials and the CTL approach are effective for improving the cognitive learning outcomes of fifth grade students at SDN 87 Lebong based on the effect size (1.24) in the very effective category.